Illustrated clinical card for the study of the facial profile (Research, Society and Development, 2023)
Facial aesthetic treatments have become increasingly common in dentistry and in order to identify discrepancies and aesthetic disharmonies that require intervention, it is necessary to know and use the reference criteria of the normality pattern of tegumentary, skeletal and dental facial structures. Based on scientifically established biometric concepts, obtained from a literature survey, this work aims to present a proposal for an illustrated clinical record for integumentary profile analysis that allows consultation of reference values and data recording (printed or digital) based on a sequence logical and rational analysis that helps professionals and academics in the diagnosis, planning and treatment of facial disharmonies in the sagittal plane. The facial profile analysis form is made up of schematic drawings, in which one can identify the types of facial profile, lip length, incisor exposure at rest (lip sealing), nasal projection, Nasion/pronasale/subnasion angle, nasio-labial angle, inter labial angle, nasion/subnasion/pogonion angle, mentolabial angle and chin-neck line. In addition to recording information obtained in the clinic or through photography, the clinical record helps in communicating with the patient. It can be concluded that the perception and recognition of anatomical structures is fundamental for the interpretation of the positive and negative points of facial analysis and that the recording of information facilitates the diagnosis and individualized planning, however, it is essential to be aware that beauty it is a subjective parameter with cultural and social influences and that the patients' desires must always be considered.